2011
DOI: 10.1007/s00103-011-1400-4
|View full text |Cite
|
Sign up to set email alerts
|

Physiologische und molekulare Mechanismen der Wirkung von körperlicher Aktivität auf das Krebsrisiko und den Verlauf einer Krebserkrankung

Abstract: Physical activity is associated with a reduced risk of colon, breast, endometrial, lung, and pancreatic cancer. Evidence for mediating molecular mechanisms from experimental studies substantially strengthens the causal inference for this relationship. Randomized controlled trials indicate that exercise affects metabolic profiles, including hormone levels (estrogen, insulin signaling), inflammation (e.g., C-reactive protein), and adipokine concentrations (e.g., leptin). The size of the effect depends frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 63 publications
(63 reference statements)
0
6
0
3
Order By: Relevance
“…In addition, the risk of colon [3, 5], breast [4, 5], and possibly endometrial, lung, and pancreatic cancer is reduced [5] (Table 2). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the risk of colon [3, 5], breast [4, 5], and possibly endometrial, lung, and pancreatic cancer is reduced [5] (Table 2). …”
Section: Introductionmentioning
confidence: 99%
“…Volume 04 Issue 8, 2020 superoxide dismutase, glutathione peroxidase, and catalase, known for their protective effects against oxidative DNA damage and carcinogenesis 87,88 . Moreover, physical activity affects the metabolic profile of estrogens which results in reduced hormonal activity and increased anti-proliferative properties in cancer cells 89 . Regular physical activity is associated with a lower risk of most common malignancies, including lung, breast, hepatobiliary tract, endometrial, colon, oropharyngeal, kidney, and bladder cancers [89][90][91] .…”
Section: Physical Activitymentioning
confidence: 99%
“…Moreover, physical activity affects the metabolic profile of estrogens which results in reduced hormonal activity and increased anti-proliferative properties in cancer cells 89 . Regular physical activity is associated with a lower risk of most common malignancies, including lung, breast, hepatobiliary tract, endometrial, colon, oropharyngeal, kidney, and bladder cancers [89][90][91] . For example, physically active men and women were found to have about a 30%-40% reduction in the relative risk of developing colon cancer compared to their inactive peers.…”
Section: Physical Activitymentioning
confidence: 99%
“…Moreover, many chronic conditions are believed to be attributable to an increasingly sedentary lifestyle. Physical activity has been hypothesized to influence thyroid cancer risk through several mechanisms [94], for example, by improving endogenous DNA repair capacity, reducing body fat, lowering insulin resistance, and altering circulating inflammatory factors [9597]. In two case-control studies, the risk of thyroid cancer was slightly reduced among subjects who reported recreational physical activity; whereas weekly frequency (hours/week) seemed to be more relevant than duration (years) in reducing risk [98].…”
Section: Risk Factors For Thyroid Cancermentioning
confidence: 99%